The Influence of ESG Controversies on Cost of Debt With The Moderating Role of ESG Performance and Corporate Governance In Asean-5 - Mustikawati, Lia; Nalurita Purnama Siregar, Sylvia Veronica (Green Publisher Indonesia, 2025)
This study investigates the impact of ESG (Environmental, Social, and Governance) controversies on the cost of debt, with a focus on the moderating roles of ESG performance, board independence, and board gender diversity. Using a sample of non-financial public companies listed on the ASEAN-5 stock exchanges from 2019 to 2023, the research explores how ESG controversies influence borrowing costs and the potential moderating effects of corporate governance mechanisms. The findings reveal that ESG controversies lead to an increase in the cost of debt, confirming the negative financial implications of such controversies. Among the corporate governance variables, only board independence is found to mitigate the relationship between ESG controversies and the cost of debt. Additionally, the results from robustness tests indicate that both board independence and gender diversity help lessen the effect of ESG controversies on debt costs. However, the moderating effect of ESG performance on the relationship between ESG controversy and the cost of debt is not supported. These findings suggest that while ESG controversies are costly for firms, strong governance practices—particularly in terms of board independence and diversity—can help reduce these financial penalties. The study contributes to the literature on corporate governance and ESG by highlighting the role of board structures in mitigating the financial costs of ESG risks.